2010
DOI: 10.3168/jds.2010-3198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementing dairy cows with chromium propionate on milk and tissue chromium concentrations

Abstract: Eight primiparous and 8 multiparous Holstein cows were used to determine the effects of Cr supplementation, in the form of Cr propionate (Cr Prop), on milk and tissue Cr concentrations. Cows were randomly assigned by parity to one of 2 diets: 1) control diet or 2) 2 mg of supplemental Cr/kg of DM. The level of Cr Prop supplemented exceeded by 4-fold the concentration of 0.5 mg of Cr/kg permitted by the FDA. Experimental diets were fed from approximately 30 d prepartum until at least 91 d postpartum, resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Hayirli et al [10] reported milk Cr levels to be between 55.4 and 56.6 μg/L in dairy cows supplemented with different levels of Cr-methionine/kg of BW 0.75 . Lloyd et al [50] found 1.7 ng/ml averaged milk Cr concentration in control and Crpropionate fed Holstein cows and was affected by day of lactation but not by Cr supplementation. Low level of Cr in milk may be due to the fact that amount transferred to milk is too low to be detected.…”
Section: Milk Mineral Content and Blood Biochemicalmentioning
confidence: 97%
“…Hayirli et al [10] reported milk Cr levels to be between 55.4 and 56.6 μg/L in dairy cows supplemented with different levels of Cr-methionine/kg of BW 0.75 . Lloyd et al [50] found 1.7 ng/ml averaged milk Cr concentration in control and Crpropionate fed Holstein cows and was affected by day of lactation but not by Cr supplementation. Low level of Cr in milk may be due to the fact that amount transferred to milk is too low to be detected.…”
Section: Milk Mineral Content and Blood Biochemicalmentioning
confidence: 97%
“…Samples of basal diet, supplements, and orts were prepared for Cr analysis by wet ashing with trace metal grade nitric acid (Trace Metal grade, Fisher Scientific, Raleigh, NC) using a hot plate digestion procedure. Chromium was measured by electrothermal atomic absorption spectrophotometry (model 6701/6601, Shimadzu, Kyoto, Japan) as described previously (Lloyd et al, 2010). The method of standard addition was used to remove matrix effects.…”
Section: Samplingmentioning
confidence: 99%
“…Chromium propionate is the only Cr source currently permitted for supplementation to cattle diets, and it can be added at levels up to 0.5 mg of Cr/kg of DM. The safety of Cr Prop has been investigated, and supplementation of lactating dairy cows with Cr Prop for 120 d at 4 times (2 mg of Cr/kg of DM) the permitted level did not increase Cr concentrations in milk, muscle, or fat (Lloyd et al, 2010). Chromium requirements of cattle, based on insulin sensitivity, are poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that Cr enhances insulin action by binding to an oligopeptide (chromodulin) that amplifies insulin receptor tyrosine kinase activity [6]. Although there is no established Cr requirement for poultry (NRC, 1997) [7], various studies involving broilers fed supplemental Cr have shown a positive effect on growth performance [8][9][10], carcass traits [8,9], and immunity [11,12] when under heat stress conditions.…”
Section: Introductionmentioning
confidence: 99%